Resenha de Território & desenvolvimento: as múltiplas escalas entre o local e o global, de Carlos Brandão, ed. da Unicamp, 238p., 2007. - Ribeiro, Guilherme (Geo UERJ, 2010)
doi: 10.12957/geouerj.2010.1465